Delimitación de la microcuenca del río Alaquez con la aplicación de sistemas de información geográfica (sig) y determinación de las necesidades hídricas para cultivos de interés. Cotopaxi, Latacunga 2019-2020. - Llasha Huaraca, Jefferson Nairovi (2020)
The present investigation was carried out in a canton zone of 22526.27 located in Latacunga city, Alaquez parish, with the purpose of determining if the water resource coming from the Alaquez river basin satisfies the amount of water for development and potato and corn production, specify as the main crops in the sector by Velasco in 2014, use a database of precipitation, temperature to calculate evapotranspiration and crop effectiveness, applying the methods of Oudin and Soil Conservation Service (USDA - SCS) respectively, with the application of Geographic Information Systems, the water resource is delimited and modeled according to topographic characteristics and soilclimatic conditions, the proposal for the construction of a reservoir is modeled. Having as a result the area of management of the place is 3652.77 ha with a management percentage of 16.22%, there is a modeling efficiency of 65% with a confidence level of 95.5%, this document applies and depends on the use of technologies for Precision agriculture development.